Analisis Komparasi Kinerja Keuangan Bank Perkreditan Rakyat (BPR) Sebelum dan Pada Pandemi Covid-19 - Ach Yasin; Ladi Wajuba Perdini Fisabilillah (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2021)
The impact of the covid-19 pandemic has reduced the economic and financial sectors. The decline has an impact of the activities and economic activities of the community. This study aims to analyze the comparison of the financial performance of rural banks (BPR) before and during the covid-19 pandemic. The research methode used is a quantitative comparative study. The result of this study are that financial performance as measured by the Loan to Deposit Ratio (LDR) and Capital Adequacy Ratio (CAR) during the pandemic is still quite healthy both before the pandemic. The relatively strong capital ratio during the pandemic explains that BPR’s are still stable in resisting the shock caused by the covid-19 pandemic. In contrast to ROA, BOPO and NPL during the pandemic, BPR’s were unable to obtain maximum profit due to the decline in lending by BPR’s, however, DPK fund obtained by BPRs actually increased and the gap suppressed profitability especially ROA. The effect of the covid-19 pandemic have made the performance of BPR inefficient because the costs incurred are greater than the income. Although the BOPO trend continues to increase during the covid-19 pandemic, it is still in the healty category. The amount of BPR’s NPL both before the pandemic and during the pandemic is quite worrying because it has a ratio of more than 5%. Based on his analysis, it can be concluded that during the pandemic, rural bank are still strong enough to withstand shock, but must always be maintained in terms of credit distribution quality and cost efficiency